Sudden unexpected cardio-respiratory arrest after venipuncture in children - Goun Jeong; Son Moon Shin; Nam Su Kim; Young Min Ahn (Korean Pediatric Society, 2018)
PurposeThis study aimed to investigate the clinical and socioenvironmental characteristics of sudden cardiorespiratory arrest after venipuncture in children.MethodsWe conducted a retrospective email-based survey of all members of the Korean Pediatric Society. The questionnaire included items on patient demographics, socioenvironmental circumstances of the venipuncture, type of cardiorespiratory arrest, symptoms and signs, treatment, prognosis, and presumed cause of the arrest.ResultsFourteen patients were identified. Of these, 13 were young children (<2 years old), and 1 was 14 years old. All patients had been previously healthy and had no specific risk factors for sudden cardiorespiratory arrest. Most cases (n=11, 79%) were defined as cardiac or cardiorespiratory arrest, while the remaining cases (n=3, 21%) were defined as respiratory arrest. Aspiration (n=3), acute myocarditis (n=2), and laryngeal chemoreflex (n=1) were presumed as the causes; however, the exact causes were unclear. The overall prognosis was poor (death, n=7; morbidity, n=5; full recovery, n=2). The medical institutions faced severe backlash because of these incidents (out-of-court settlement, n=5; medical lawsuit, n=5; continuous harassment, n=3).ConclusionCardiorespiratory arrest after venipuncture is unpredictable and the probable cause of most cases is a vasovagal reaction. Medical personnel must be aware of the risk of unexpected cardiorespiratory arrest during routine intravenous procedures.